Fourth generation neutrinos and neutrino induced hadron production in the resonance region - Schalla, Dario (Technische Universität Dortmund, 2013)
We investigate two aspects in neutrino physics. First, we consider the extension of the standard model by a fourth fermion generation. Allowing finite mixing of the additional neutrino, which is kept most general with a Majorana mass term, constraints on the size of its Majorana mass are derived by its contribution in neutrinoless double beta decay. This determines the neutrino to be a pseudo-Dirac particle and implications for lepton number violating processes are discussed. After constraining the mixing matrix elements by radiative charged lepton decays we present an extradimensional model for softening the horizontal neutrino mass hierarchy. Then we study the consequences of the neutrino in baryogenesis, where a similar bound on the Majorana mass is obtained by estimating the washout effect on any baryon- or lepton-asymmetry. The second topic is the production of pions by neutrino-nucleon interactions via resonances. For this process various cross sections, including nuclear corrections and pion spectra, are calculated and possible applications to CP searches are proposed.

Wir untersuchen zwei Aspekte der Neutrinophysik. Zunächst betrachten wir die Erweiterung des Standardmodells durch eine vierte Generation von Fermionen. Wir erlauben eine endliche Mischung des zusätzlichen Neutrinos, welches möglichst allgemein mit Majoranamasse gehalten wird, und leiten durch dessen Beitrag zum neutrinolosen Doppelbetazerfall Beschränkungen für die Größe der Majoranamasse her. Dies legt fest, dass das Neutrino ein pseudo-Dirac Teilchen sein muss. Die Auswirkungen auf die Leptonenzahl verletzende Prozesse werden diskutiert. Nach einer Beschränkung der Elemente der Mischungsmatrix durch radiative Zerfälle geladener Leptonen präsentieren wir ein Model mit Extradimensionen, welches die horizontale Hierarchie der Neutrinomassen abschwächt. Anschließend untersuchen wir die Konsequenzen des Neutrinos für die Baryogenese, wo eine ähnliche Grenze für dieMajoranamasse abgeleitet wird, indem der Auswascheffekt für Baryon- oder Leptonenasymmetrien abgeschätzt wird. Das zweite Thema ist die Produktion von Pionen durch Neutrino-Nukleon Wechselwirkungen durch die Erzeugung von Resonanzen. Für diesen Prozeß werden verschiedene Wirkungsquerschnitte, inklusive nuklearer Korrekturen und Pionenspektren, berechnet und eine Anwendung für CP Suchen vorgeschlagen.
Keywords: Delta resonance; Fourth generation; Neutrino; Neutrinoless double beta decay; PCAC; Pionproduction; 530